THE EFFECTIVENESS OF TRAINING FROM HOME ON VO2MAX FEMALE VOLLEYBALL ATHLETES - Meyke Parengkuan; Abdul Rahman Lahay (Universitas Negeri Gorontalo, 2022)
This study aims to determine the effectiveness of Training From Home (TFH) on vo2max female volleyball athletes at SMP Negeri 13 Gorontalo City. This study uses a quasi-experimental approach that uses a population of all female athletes at SMP Negeri 13 Gorontalo, totaling 16 athletes, who were then divided into an experimental group and a control group of 8 athletes each who were randomly selected. This instrument uses the Multistage Fitness Test (MFT) and uses skipping as a treatment. Analysis of research data using paired sample t-test or t-test using SPSS 20. The results of this study can be concluded that there is a significant difference in the effectiveness of TFH exercise on VO2Max